Application of Augmented Reality Learning Media to Overcome the Learning Difficulties of the Golden Generation - Ihfanti Fidya (Cakrawala Repositori IMWI, 2024)
Education is the right of every human being in order to develop. The point is that education cannot be separated because it originates from human life on this earth. Every human being who is born into this world needs education, through the process of transferring knowledge and applying knowledge which a teacher must carry out with students. The role of teachers is very important in choosing the future of their students, becoming prospective golden generations who hold the baton for the future of the Indonesian nation. In the educational process, a teacher who is creative and innovative is needed to implement learning activities that support an interactive process when learning, this is due to the fact that there are still many prospective golden generations who have difficulties when studying. a teacher must be able to have the competence to master learning examples and learning methods, based on data from the evaluation of the Teacher Competency Test to measure and determine the extent to which the competence of teachers from elementary school teachers, junior high school teachers, to high school teachers is very worrying, namely below the standard value. minimum 75. Teacher competency consists of student understanding, mastery of learning material, educating students in learning, teacher personality and teacher professionalism, application of learning examples is included in teacher professionalism. If teacher competency is still below the minimum score of 75, it means that there are still many teachers who cannot apply learning media. A teacher should be able to use examples of perfect learning media to handle children who tend to be active. This happens because a teacher has not been able to implement examples of synchronous learning media for his students, so students experience learning difficulties.